Morbidity, mortality, and health-seeking behaviour in rural Senegal: local understanding and representation of disease across method of treatment - Dr. John Sandberg, PhD; Sadio Ba Gning, PhD; Loubna Belaid, MPH (Elsevier, 2014)
Background: Ethnomedical nosologies in many parts of the world, including west Africa, encompass both naturalistic (related to mechanisms of contagion and pollution) and personalistic (related to spiritual and supernatural malevolence) causes that are at times fundamentally at odds with the biomedical model. We explored cultural models in a rural population in the Fatick region of Senegal related to the use of ethnomedical and biomedical therapies and examine dimensionality of schemas and associated behaviours motivating and affected by the choice of therapeutic model. Methods: We collected innovative disease-narrative histories as part of the Niakhar Social Networks and Health Project (NSNHP) from more than 100 in-depth semistructured interviews held with a random sample of area residents aged 16-91 years. These interviews, transcribed and extensively coded for computer-assisted analysis, contain information about the use of interpersonal resources and helping around illnesses, symptomology, perceived causes of illness, and treatment options pursued, their costs, respondents' understanding of them, and their perceived efficacy. We compared schemas and behaviours surrounding treatment in biomedical institutions (pharmacies, health centres, and hospitals) with those in ethnomedical intuitional settings (traditional spiritual healers, ethnobotanical practitioners, oracles, and religious healers). Findings: Health seeking behaviour in this population is not restricted exclusively to biomedical or ethnomedical treatment. Rather, individuals and families seek efficacious solutions to illness and medical crises from both sequentially or simultaneously, with indigenous cultural schemas concerning nosology supportive of both ethnomedical and to a lesser extent (particularly in the case of infectious disease) biomedical treatment. At the same time, we noted a near universal duality of cause and treatment; certain illnesses are perceived to be treatable only by ethnomedical, others only by biomedical therapy. We report that although perceived cause can affect choice of therapeutic venue, perceived efficacy of previous treatment (both proximal and within respondents' social networks) could be equally responsible for shaping schemas invoked by respondents when discussing their illness and choice of therapeutic venue. Interpretation: Insights such as those gained here could be used to develop measures of cultural and ideational context for use in survey-based demographic and health research projects, using the example of the instrument developed for the NSNHP. Funding: National Institute of General Medical Sciences.